Advances in Biological Function and Clinical Application of Small Extracellular Vesicle Membrane Proteins - Huang, Defa; Chen, Jie; Hu, Die; Xie, Fangfang; Yang, Tong; Li, Zhengzhe; Wang, Xiaoxing; Xiao, Yongwei; Zhong, Jianing; Jiang, Yu; Zhang, Xiaokang; Zhong, Tianyu (Frontiers in Oncology, 2021)
Small extracellular vesicles are membrane-bound vesicles secreted into extracellular spaces by virtually all types of cells. These carry a large number of membrane proteins on their surface that are incorporated during their biogenesis in cells. The composition of the membrane proteins hence bears the signature of the cells from which they originate. Recent studies have suggested that the proteins on these small extracellular vesicles can serve as biomarkers and target proteins for the diagnosis and treatment of diseases. This article classifies small extracellular vesicle membrane proteins and summarizes their pathophysiological functions in the diagnosis and treatment of diseases.